Upaya Peningkatan Keterampilan Narapidana sebagai Bentuk Pembinaan Kemandirian di Rutan Kelas IIB Banjarnegara - Michael M Rahardjo; Umar Anwar (Indonesian Journal of Social Science Education (IJSSE), 2022)
The congested condition of the Class IIB Banjarnegara State Detention House (Rutan) is contradictory with the hope of providing maximum skills. The number of prisoners is not proportional to the officers and potential of the detention center. So with these conditions it does not provide maximum independence development. The purpose of this study was to determine the efforts to improve the skills of prisoners as a form of independence development at the Class IIB Banjarnegara Rutan. The method used is a phenomenological approach, through qualitative methods with interviews, observations and literature studies in data collection, data analysis techniques through the reduction stage, the results show that the strategy for improving the skills of prisoners carried out at the Class IIB Banjarnegara Rutan is through the existing independence development strategy. in prison. The results of the analysis show that the implementation of the Convict Skills Development program as a Form of Independence Development at the Banjarnegara Class IIB Rutan is currently ongoing even though in the midst of the Covid-19 pandemic, the coaching program at the Banjarnegara Class IIB Rutan is divided into 2 (two) namely Personality Development and Independence Development. Skill development through self-reliance development activities is expected to create skilled and independent correctional inmates.